Pengaruh Kualitas Produk Terhadap Kepuasan Konsumenpada CV. Retina Printing Di Bandar Lampung - Sapmaya Wulan; Abizar Alghifari (JURNAL TEKNIK INDUSTRI, 2011)
The survival of firm is influenced by customer satisfaction. One element that could affect customer satisfaction is the quality of the product. CV. Retina Printing in Bandar Lampung is a company engaged in the printing. The company is always trying to get the product produced can provide satisfaction to consumers, especially in terms of quality products. Elements of the quality of the product include: a) materials used; b) the design is interesting, c) machinery; d) process of the professionals (creative, skilled, thorough and direct technicians); e) printout (clear, adhesive durable and waterproof). Customer satisfaction with quality of products includes the following elements: quality, price, punctuality and service. The company strives to maintain and improve the quality of its products, but still faces problems such as: the number of consumer complaints against the total number of consumers who are, respectively: the quality (1.91%), price (1.8%), accuracy (3.08%) and services (2.45%), higher than the standard number of consumer complaints that the company determined that 1.5%. This shows that customer satisfaction with the quality of the resulting product is still not fully in line with expectations or standards specified company.The problem is: How does product quality on the level of consumer satisfaction in the CV. Retina Printing in Bandar Lampung. The objectives of this study to determine how the influence of product quality to customer satisfaction rate on the CV. Retina Printing Bandar Lampung. This study uses qualitative and quantitative methods. In the analysis of qualitative analysis are used tables and in quantitative models used Cartesian diagram (Importance Performance Analysis). From the results of qualitative analysis can be concluded that the quality of the products in the category / criteria is in accordance with the expectations of consumers, although there are attributes that are still needed. From the results of quantitative analysis with the calculation of Importance Performance Analysis to know the average overall level of consumer expectation of 4.10 greater than the average level of overall product quality which is equal to 4.07. Although the calculated relative differences are very small ie 0.03, this suggests that the quality of the products has not been fully in line with expectations of consumers. In other words, the quality of the product affects the customer satisfaction. Thus the hypothesis that product quality has a positive effect on the level consumer satisfaction on the CV. Retina Printing in Bandar Lampung is acceptable.